Functional re-education in Spanish Spas - Corvillo Martín, Inmculada; Aguilera López, Lourdes; Martín Megías, Ana Isabel (Anales de Hidrología Médica, 2012)
The present study pretends to know, first hand from within each establishment, the different sanitary methods offered, paying special attention to certain techniques and certain pathologies. A specific questionnaire was elaborated and the medical directors of ninety three Spanish spas were contacted. With the information obtained, organized and elaborated, we have come to know the true present situation of Spanish Spas, the technical and professional methods used, the pathologies treated, the crenotherapy treatments applied and the different functional reeducation programs applied to the locomotor, respiratory, and ORL system, as well as the Sanitary and Social-sanitary offer.